Weight Gain Outcomes Following Surgical Management of Laryngomalacia in Pediatric Patients: A Systematic Review - Ahmed, Nehad J. (Asian Journal of Pharmaceutics (AJP), 2025)
Laryngomalacia is the most common congenital upper airway disorder in infants, characterized by dynamic supraglottic collapse, causing inspiratory stridor, feeding difficulties, and failure to thrive (FTT). While mild cases resolve spontaneously, severe cases often require surgical intervention. Supraglottoplasty, the gold- standard surgical treatment, alleviates airway obstruction, improves feeding efficiency, and promotes weight gain. However, outcome variability and methodological differences highlight the need for a systematic review. This review evaluates supraglottoplasty’s efficacy and safety in severe laryngomalacia, focusing on weight gain, feeding efficiency, respiratory improvement, and complications. Following Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines, PubMed and Cochrane Library were systematically searched for studies on pediatric patients undergoing supraglottoplasty. Data on weight gain, feeding, respiratory outcomes, and complications were extracted, and quality was assessed using the Newcastle–Ottawa scale. Thirteen studies (706 patients) were included. Mean age at surgery ranged from 2 weeks to 15.6 months. Weight gain improved significantly, with percentile increases of 15–26 points, particularly in infants <6 months. Feeding efficiency improved in 96% of cases, and respiratory symptoms resolved in >90%. Complication rates were low (<5%), with transient dysphagia being most common. No major adverse events were reported. Supraglottoplasty effectively improves weight gain, feeding, and respiratory outcomes in severe laryngomalacia, with a strong safety profile. Early intervention is crucial for optimal growth, especially in FTT cases. Further research, including randomized trials, is needed to standardize outcomes and refine techniques for complex cases